The Influence of Disturbance Dynamo Electric Field in the Formation of Strong Sporadic E Layers Over Boa Vista, a Low‐Latitude Station in the American Sector. Issue 7 (24th June 2020) - Resende, L. C. A.; Shi, J. K.; Denardini, C. M.; Batista, I. S.; Nogueira, P. A. B.; Arras, C.; Andrioli, V. F.; Moro, J.; Da Silva, L. A.; Carrasco, A. J.; Barbosa, P. F.; Wang, C.; et al.
Abstract: This study analyzes strong sporadic E layer (Es) formation in Boa Vista (BV, 2.8°N, 60.7°W, dip: 18°), a low‐latitude region in the Brazilian sector, which occurred far after the onset of a magnetic storm recovery phase. Such occurrences were observed during seven magnetic storms with available data for BV. Thus, the ionospheric behavior on days around the magnetic storm that occurred on 20 January 2016 was investigated to search for possible explanations. This analysis indicated that the probable mechanism acting during the Es layer strengthening is the zonal westward electric field caused by a disturbance dynamo. The same evidence was also observed in two other magnetic storms at the same location. Hence, a numerical model of the E region dynamics, called MIRE (Portuguese acronym for E Region Ionospheric Model), was used to confirm whether the disturbance dynamo could cause the Es layer intensification. The inputs for the model were the electric field deduced from the vertical drift and the wind components provided by GSWM‐00 model. The simulations indicate that the Es layer density is significantly enhanced when the zonal electric field is present compared to the reference scenario with only the winds. Therefore, it is concluded that the disturbance dynamo electric field is the likely cause of the strong Es layers in the analyzed cases. Finally, the combined results from the model and observational data seem to contribute significantly to advance our understanding of the role of the electric fields in the Es layer formation at low latitudes. Key Points: Data analysis and modeling taking into account wind and E field are employed to study anomalous Es layers in Boa Vista The results show that the most probable mechanism responsible for the Es layer strengthening in Boa Vista is the zonal westward electric field caused by the disturbance dynamo Simulations support our assumption that the disturbance dynamo electric field leads the observed Es layer intensification in Boa Vista